Cultura financiera y comunicación comercial de productos financieros en los vendedores del mercado Oscar Iván asentamiento humano Manuel Cardozo Dávila distrito de Belén año 2023 - Guevara Isuiza, Roddy Cristoper (2024)
The objective of this research was to determine the relationship between financial culture and commercial communication of financial products among the vendors of the Oscar Iván Market, Asentamiento Humano Manuel Cardozo Dávila, district of Belén, year 2023. In this sense, the methodology applied comprised a basic type, quantitative approach, correlational and non experimental design, as well as a sample composed of 131 participants among merchants of the Oscar Ivan Market of Iquitos and independent experts on financial culture and commercial communication with the purpose of applying the data collection instrument, after resorting to the application of a probabilistic sampling. The main results demonstrated the importance of promoting a financial culture (based on financial knowledge, behavior and attitude) in order to foster commercial communication (materialized through nuances such as communication with the client, persuasion towards the purchase and client loyalty) with competent entities regarding the acquisition of financial products by the sellers of the Óscar Iván Market in Iquitos. Finally, the main conclusion was that there is a significant relationship between financial culture and commercial communication of financial products among the vendors of the Oscar Iván Market, Asentamiento Humano Manuel Cardozo Dávila, Belén district, year 2023. This conclusion is based on the Spearman Correlation index established for the general hypothesis, whose value was 0.988.